The effect of nanofiller addition to an experimental dentin adhesive on microtensile bond strength to human dentin - SH. Kasraei; M. Atai; Z. Khamverdi; S. Khalegh Nejad (Tehran University of Medical Sciences, 2009)
Objective: The purpose of the study was to evaluate the influence of adding nanofiller particles to a dentin bonding agent on resin-dentin bond strength. Materials and Methods: Fifty-four human intact premolar teeth were divided in to 6 groups of nine. The teeth were ground on occlusal surfaces and polished with 320 and then 600 grit silicon carbide papers. An experimental bonding system based on acetone/alcohol solvent was provided with filler contents of 0.0, 0.5, 1.0, 2.5, 5.0, and 10.0 weight percent fumed silica nanofiller. After dentin surface etching, rinsing and blot drying, the experimental bonding agents were applied to dentin surface. A composite resin was, then, bonded to the dentin on the bonding agent. The specimens were thermocycled for 500 cycles and sectioned in stick form. After two week of storage in distilled water, resin-dentin microtensile bond strength of the specimens was measured. Data were analyzed by one way ANOVA and DunnettT3 tests. Results: Bond strength to dentin was significantly affected by the filler level. Minimum and maximum resin-microtensile bond strength was in the experimental bonding agent with no filler (5.88 MPa) and with filler level of 1.0 weight percent (15.15 MPa), respectively and decreased with the increase of filler content down to 8.95 MPa for the filler level of 10.0 weight percent. Conclusion: Filler content seems to be one of the important factors influencing the bond strength of dental adhesives. Maximum dentin bond strength was obtained with 1% silanized nanofiller silica added to experimental adhesive system.